ASSOCIATION BETWEEN CERTAIN DEMOGRAPHIC INDEXES AND THE NUMBER OF CLINICAL TRIALS IN THE EUROPEAN ECONOMIC AREA - Liliya Bogdanova; Valentina Belcheva; Evgeni Grigorov (Peytchinski Publishing, 2021)
Purpose: The number of clinical trials conducted by the industry has increased significantly for the period 2014-2016. They have produced advances in disease prevention, treatment, and rehabilitation for many diseases. This was the main reason to carry a study on the association between certain demographic indexes and the number of clinical trials in the European economic area. Proving a correlation between those two variables could lead to additional research pursued by the industry during the feasibility phase of each study in order to have higher and quicker enrollment for the success of the clinical trial. Materials/Methods: Three demographic factors were considered to have some importance on the clinical trial enrollment - the number of population, life expectancy at age 65 and Disability-Adjusted Life Years (DALY). The numbers were processed with Spearman'rho, and the read of the results shows a correlation to be present for the number of population and life expectancy at age 65. Results: There is a correlation between the number of clinical trials opened for enrollment of patients and certain demographic indexes, which could lead to favorable conditions for trial conduct in the different countries of EEA. Conclusions: Studying in advance if some demographic factors are significant for conduct of clinical studies is something new that could be used by the industry to avoid the wastefulness of a clinical project.